ON THE PROBLEM OF AESTHETIC CATEGORIES IN THE SCIENCE FICTION WORKS OF VYACHESLAV RYBAKOV - Kuchinsky A.Yu. (International Journal of Literature and Language Studies, 2026)
This article examines the problem of aesthetic categories and their embodiment in the modern science fiction novel using the work of Russian science fiction writer Vyacheslav Rybakov as an example.